Analysis and application of the CASA IP1 X-band polarimetric radar network - Dolan, Brenda, author; Rutledge, Steven A., advisor (Colorado State University. Libraries, 2009)
The Collaborative Adaptive Sensing of the Atmosphere's Integrated Project 1 (CASA IP1) network of four X-band, polarimetric, Doppler, adaptively scanning radars is investigated for studying storm microphysics and kinematics. The complications of non-Rayleigh scattering and attenuation at X-band are explored for impact on microphysical interpretation. The rapid and adaptive scanning strategy is evaluated for application of dual-Doppler techniques to retrieve the 3-D wind field, and general understanding of storm interactions. Several rain rate algorithms are invoked to estimate surface rainfall. A case study from 10 June 2007 illustrates the capabilities and limitations of using the IP1 network for studies of storm interactions, and lightning data are analyzed to relate these interactions to storm electrification. The nearby S-band, polarimetric KOUN radar is studied for comparison. Scattering simulations using the T-matrix model are performed on seven hydrometeor types (excluding hail) to understand the non-Rayleigh effects at X-band compared with S-band. The simulations show the greatest non-linearities in Zdr and Kadp of rain and graupel. Results of the simulations are used to develop a specific X-band fuzzy logic hydrometeor identification algorithm (HID) for diagnosing bulk regions of hydrometeors. Attenuation and non-Rayleigh scattering are present in the IP1 data, but with mitigation techniques these have minimal impact on the analysis. The high temporal resolution is integral in resolving up- and downdrafts, as well as hydrometeor evolution, but the inconsistent and lack of upper-level coverage are significant limitations for quantitative analysis of kinematic and microphysical relationships. Observations using IP1 data of a storm on 10 June 2007 show the development of the updraft, subsequent graupel echo volume evolution, and onset of lightning. Development of the downdraft is preceded by large volumes of graupel in the mid-levels. A second peak in intra-cloud lightning is observed to be associated with an increase in height of the upper positive charge, resulting from a kinematic intensification. Many of these trends are corroborated by KOUN. Rain rate estimation comparisons show that the X-band blended algorithm performs better compared with ground-based sensors than the simple Z-R relationship and employs polarimetric estimators more often than S-band blended methods.
Keywords: CASA ip1; polarimetric radar network; storm evolution; surface rainfall; atmospheric sciences; remote sensing